PENERAPAN MODEL PEMBELAJARAN PAIR CHECKS SPENCER KAGEN 1993 UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII MATA PELAJARAN FIQIH DI MTS. BABUSSALAM SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI. - Aswandri Pramana; Bustanur Bustanur (Universitas Islam Kuantan Singingi, 2020)
This Classroom Action Reasearch (CAR) is based on the low students’ motivation in teaching and learning process, especially in Fiqh Subject at the eight grade in MTs. Babussalam Simandolak Benai District. To solve that problems, then the teacher needs to apply an appropriate learning model so that it can overcome the problems to increase students’ motivation. One of learning model that can be applied is Checks Spencer Kagen 1993. The purpose of this research is to find out how the application of learning model of Checks Spencer Kagen 1993 to increase students’ motivation at the eight grade on Fiqh Subject. The subject of this research is a teacher of Fiqh subject that teach in MTs. Babussalam Simandolak Benai District Kuantan Singingi Regency and all the students of eight grade, with the total students are thirty students. Meanwhile the object of the research is the application of learning models of Pair Checks Spencer Kagen 1993to increase students’ motivation at the eight grade on Fiqh Subject at MTs. Babussalam Simandolak, Benai District. Then the population of the research is a teacher of Fiqh Subject and all the students of eight grade with the total students are thirty students consist of fourteen boy students and sixteen girl students. Because the population of this research less than one hundred, so the researcher take the sample as a whole is thirty students with the sampling technique is total sampling or this research is called population research. The result is :The application of learning models of Pair Checks Spencer Kagen 1993to increase students’ motivation at the eight grade on Fiqh Subject at MTs. Babussalam Simandolak have been done well. It can be seen from the result of first observation which is implemented, seen from ten item that have been observed, only four item which is implemented perfectly while six item have not been implemented yet. At the second observation only six item which is implemented perfectly while four item have not been implemented yet while at the third observation seen that all the items have been done perfectly by the teacher of Fiqh Subject, The application of learning models of Pair Checks Spencer Kagen 1993to increase students’ motivation at the eight grade on Fiqh Subject at MTs. Babussalam Simandolak can increase the students’ motivation at the eight grade on Fiqh Subject, it can be proved from pre cycled only 20,99% students who have good motivation. First cycled is increasing into 36,66%. Second cycled is increasing into 70,66% and the third cycled is more increasing into 85,66%. Keyword: the application of learning models of Pair Checks Spencer Kagen 1993 and students’ motivation